Reperfusion Promotes Mitochondrial Biogenesis following Focal Cerebral Ischemia in Rats - Xie, Yuying (Public Library of Science, 2014)
BACKGROUND AND PURPOSE: Reperfusion after transient cerebral ischemia causes severe damage to mitochondria; however, little is known regarding the continuous change in mitochondrial biogenesis during reperfusion. Mitochondrial biogenesis causes an increase in the individual mitochondrial mass of neurons and maintains their aerobic set-point in the face of declining function. The aim of this study was to examine mitochondrial biogenesis in the cortex during reperfusion following focal cerebral ischemia. METHODS: Male Wistar rats were subjected to transient focal cerebral ischemia. The relative amount of cortical mitochondrial DNA was analyzed using quantitative real-time PCR at 0 h, 24 h, 72 h, and 7 d after reperfusion. Three critical transcriptional regulators of mitochondrial biogenesis were measured by semi-quantitative reverse-transcription PCR. The protein expression of cytochrome C oxidase subunits I and IV was detected by Western blotting. RESULTS: Evidence of increased mitochondrial biogenesis was observed after reperfusion. The cortical mitochondrial DNA content increased after 24 h, peaked after 72 h, and maintained a high level for 7 d. The cortical expression of three critical genes for the transcriptional regulation of mitochondrial biogenesis, namely, peroxisome proliferator-activated receptor coactivator-1α, nuclear respiratory factor-1, and mitochondrial transcription factor A, also increased at 24 h and 72 h. The expression of peroxisome proliferator-activated receptor coactivator-1α returned to the baseline level at 7 d, but two other factors maintained higher levels compared with the controls. Moreover, the expression of cytochrome C oxidase subunits I and IV was increased in the cortex. CONCLUSIONS: These results indicate that reperfusion increased mitochondrial biogenesis following focal cerebral ischemia, and this tendency was exacerbated as the reperfusion time was extended. Reperfusion-induced mitochondrial biogenesis was mediated through up-regulation of critical transcriptional regulators of mitochondrial biogenesis.